2009
DOI: 10.1016/s0079-6417(08)00002-4
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Dynamics in Rotating Helium Superfluids

Abstract: New techniques, both for generating and detecting turbulence in the helium superfluids 3 He-B and 4 He, have recently given insight in how turbulence is started, what the dissipation mechanisms are, and how turbulence decays when it appears as a transient state or when externally applied turbulent pumping is switched off. Important simplifications are obtained by using 3 He-B as working fluid, where the highly viscous normal component is practically always in a state of laminar flow, or by cooling 4 He to low … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 132 publications
1
26
1
Order By: Relevance
“…Krusius et al conducted a series of experimental studies on QT in superfluid 3 He-B under rotation [61][62][63][64][65][66] and observed the strong temperature-dependent transition of a few seed vortices to turbulence. A seed vortex can develop into turbulence when the temperature is lower than the onset temperature T on , whereas the seed vortex does not lead to turbulence above T on .…”
Section: Temperature-dependent Transition To Qtmentioning
confidence: 99%
“…Krusius et al conducted a series of experimental studies on QT in superfluid 3 He-B under rotation [61][62][63][64][65][66] and observed the strong temperature-dependent transition of a few seed vortices to turbulence. A seed vortex can develop into turbulence when the temperature is lower than the onset temperature T on , whereas the seed vortex does not lead to turbulence above T on .…”
Section: Temperature-dependent Transition To Qtmentioning
confidence: 99%
“…QT physics, comprising tangled quantized vortices, is an important research topic in lowtemperature physics [8,9]. Stimulated by recent experiments on both superfluid 3 He and superfluid 4 He, where a few similarities have been observed between quantum and classical turbulence [10][11][12][13][14][15][16][17], studies on QT have entered a new stage where one of the main motivations is to investigate the relationship between quantum and classical turbulence. In particular, the Kolmogorov-Obukhov turbulent kinetic energy spectrum E(k) ∝ k −5/3 has been observed in laboratory experiments on superfluid 4 He similar to that in normal fluids [18].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was observed in many experiments, from the quantum turbulence created by the heat load [14,15,23] up to turbulent front of uniform vorticity in a rotating 3 He [24,25]. A key assumption is that the propagation of the front occurs in the manner of a diffusion, with the source of the vortices behind the front.…”
Section: Propagation Of the Turbulent Frontsmentioning
confidence: 91%